Our roots are still alive ([Manila Asian Social Institute Communication Center, 1981)
Shows the Muslims being displaced in Philippine society due to continuous conflicts in Mindanao. They are also treated as refugees in their own land as a result of the military's drive against the so-called terrorists in the area.
Keywords: Victims of terrorism -- Philippines -- Mindanao; Muslims -- Philippines -- Mindanao; Sociology; Philippine history